2015
DOI: 10.1007/s40263-015-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone: A Review of Its Use in Adult Patients with Bipolar I Depression

Abstract: Lurasidone (Latuda(®)), a benzisothiazole derivative antipsychotic, is approved in the USA and Canada for the treatment of adults with major depressive episodes (MDE) associated with bipolar I disorder; this article reviews studies of lurasidone in this indication. In two 6-week, placebo-controlled trials in adults with bipolar I depression, lurasidone 20-120 mg/day reduced depressive symptoms, either as monotherapy or as an adjunct to lithium or valproate. Lurasidone reduced the mean Montgomery-Åsberg Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…4 The effective low doses in our study are consistent with the successful dose ranges reported in the FDA clinical trials of acute antidepressant effects of lurasidone. 8 Our results also confirm that lurasidone has a favorable benefit-risk ratio in both acute and maintenance treatment of BD MDE. The most significant common adverse effects during both phases were overactivation in nature.…”
Section: Discussionsupporting
confidence: 79%
“…4 The effective low doses in our study are consistent with the successful dose ranges reported in the FDA clinical trials of acute antidepressant effects of lurasidone. 8 Our results also confirm that lurasidone has a favorable benefit-risk ratio in both acute and maintenance treatment of BD MDE. The most significant common adverse effects during both phases were overactivation in nature.…”
Section: Discussionsupporting
confidence: 79%
“…Whilst lamotrigine has been found to be effective for some patients with BD II, for other patients it may not provide any benefit. Atypical antipsychotic medications such as quetiapine, olanzapine and lurasidone, have shown significant benefits in bipolar depression (Level II) (Azorin et al, 2013; Bawa and Scarff, 2015; Janicak and Rado, 2011; Loebel et al, 2014a; Sanford and Dhillon, 2015; Sanford and Keating, 2012; Tohen et al, 2013; Vieta and Valenti, 2013). Asenapine may also be helpful (Azorin et al, 2013).…”
Section: Clinical Management Of Mood Disorders With Complex Presentatmentioning
confidence: 99%
“…Response to a single ketamine infusion appears within minutes but does not last more than 3 to 4 days (Young et al, 2000; Diazgranados et al, 2010; Zarate et al, 2012; Loebel et al, 2014b; Xu et al, 2015a). However, there is one unpublished failed study with lurasidone as add-on to lithum or valproate (Suppes et al, 2013; Sanford and Dhillon, 2015). A small placebo-controlled adjunctive study of aripiprazole to lithium and citalopram was negative.…”
Section: Efficacy Datamentioning
confidence: 99%